2019
DOI: 10.3390/nu11112735
|View full text |Cite
|
Sign up to set email alerts
|

Do Consumers Care about Nutrition and Health Claims? Some Evidence from Italy

Abstract: This study investigates Italian consumer knowledge and use of nutrition and health claims (NHCs). Six specific claims are examined on the basis of a web survey carried out on a sample of 504 consumers. Our results show that there is little attention to NHCs and their use is not widespread; objective knowledge of the selected claims is fairly scant, generating misinterpretation and confusion about their real meaning. K-means cluster analysis allowed us to identify three segments of consumers, characterized by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…The existing literature addressed the cognitive processes correlated with the effects of food labels and the role of nutritional labels in driving consumers’ healthy food choices [ 24 , 25 ]. Although information about the nutritional content of food has a strong influence on consumers’ choices of healthier food products [ 26 ], in many cases, the nutrition information provided on such labels is underutilized by consumers due to their limited amount of objective knowledge [ 4 , 19 , 25 ].…”
Section: Literature On Antioxidants and Health Claims On Olive Oilmentioning
confidence: 99%
See 2 more Smart Citations
“…The existing literature addressed the cognitive processes correlated with the effects of food labels and the role of nutritional labels in driving consumers’ healthy food choices [ 24 , 25 ]. Although information about the nutritional content of food has a strong influence on consumers’ choices of healthier food products [ 26 ], in many cases, the nutrition information provided on such labels is underutilized by consumers due to their limited amount of objective knowledge [ 4 , 19 , 25 ].…”
Section: Literature On Antioxidants and Health Claims On Olive Oilmentioning
confidence: 99%
“…In addition, a recent paper pointed to the coexistence of different market segments with different levels of sensitivity to nutrition and health claims, thus identifying potential claim users, actual claim users, and non-users [ 4 ]. Conversely, the role of health claims in consumers’ olive oil choices is quite under-researched.…”
Section: Literature On Antioxidants and Health Claims On Olive Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…Some factors related to customers may also be important to the effect of NCs. Nutrition knowledge, motivation to adopt a healthy diet, health consciousness and consumers’ difficulty to understand claims may modulate the effect of NCs [ 9 , 10 , 13 , 14 , 15 , 16 ]. As a summary of all the potential factors influencing the effect of NCs on food choices, Oostenbach proposed a conceptual model in 2019 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the least important claim was "low salt". Annunziata and Mariani [13] examined six specific claims on the basis of a web survey carried out on a sample of 504 consumers. Findings revealed that there is little attention paid to nutritional health claims and their use is not widespread.…”
mentioning
confidence: 99%